Pediatrics Upper Gastrointestinal Endoscopy Profile in Riau in 2020 and 2021 - Deddy Satriya Putra (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Children's limited communication skills when expressing complaints often limit healthcare practitioners in making diagnoses and treatment decisions, particularly regarding gastrointestinal issues.  Endoscopy is a valuable tool for determining the appropriate course of action in these cases. This study aims to describe the characteristics of pediatric patients who underwent upper gastrointestinal endoscopic procedures in Riau between 2020 and 2021. Methods: This retrospective study used secondary data from endoscopy registries and patient medical records at two tertiary hospitals in Riau between Januari 2020 to December 2021. Results: A total of 114 patients underwent upper gastrointestinal endoscopy from 2020 to 2021. It was found that the adolescent age group (42%) was the most frequently encountered group. The female sex (65%) was more prevalent than male. Meanwhile, the most common problem encountered was abdominal pain (57%). Gastroscopy alone was the most frequently performed procedure in this study (65%), with the most common endoscopic finding being hyperemic gastritis (54%). Conclusion: Upper gastrointestinal endoscopy in pediatric patients is a safe and very helpful procedure in diagnostics and therapeutics.